Burnout in New Zealand resident doctors: a cross-sectional study of prevalence and risk factors - Denys Shay; Susanna Every-Palmer; Alex B Boyle; Tanushk Martyn; Earle Savage; Simon B M MacLean (BMJ Open)
Objective Burnout syndrome, characterised by emotional exhaustion, depersonalisation and decreased personal accomplishment, is well documented in the medical workforce. This study aimed to investigate the prevalence of burnout in New Zealand resident doctors (doctors who have yet to complete their specialty training).Design Cross-sectional survey study of resident doctors in New Zealand.Setting Distributed by email.Participants 509 resident doctors currently working in New Zealand. Doctors not currently working or those who have completed their specialty training (consultants) were excluded.Primary and secondary outcome measures Participants were asked about a number of demographic and work-related factors and to complete the Maslach Burnout Inventory, which measures the three dimensions of burnout: ‘Emotional Exhaustion’, ‘Depersonalisation’ and low ‘Personal Accomplishment’.Results 409/509 (80%) of respondents had scores indicating high burnout on at least one dimension. 163 (32%) had high burnout on one dimension, 111 (22%) on two dimensions and 135 (26%) on all three dimensions. Feeling well supported protected against burnout in all three dimensions: emotional exhaustion (OR 0.34, CI 0.19 to 0.60), depersonalisation (OR 0.52, CI 0.31 to 0.86) and decreased personal accomplishment (OR 0.51, CI 0.29 to 0.78). Having a manageable workload protected against emotional exhaustion (OR 0.23, CI 0.13 to 0.37) and depersonalisation (OR 0.39, CI 0.24 to 0.61). Increasing weekly exercise was protective for personal accomplishment (OR 0.846, CI 0.73 to 0.98). Having children was protective for depersonalisation (OR 0.7, CI 0.53 to 0.90). A personal history of depression or anxiety was associated with burnout on all three dimensions: emotional exhaustion (OR 2.86, CI 1.67 to 5.00), depersonalisation (OR 1.66, CI 1.01 to 2.73) and decreased personal accomplishment (OR 1.71, CI 1.05 to 2.80). Alcohol misuse was associated with an increased risk of depersonalisation (OR 1.68, CI 1.08 to 2.62), and feeling inadequately remunerated was associated with emotional exhaustion (OR 2.27, CI 1.28 to 4.17). Qualitative data revealed concerns about poor staffing, inadequate remuneration, a focus on service provision over education, slow career progression and difficulty balancing work and specialty examinations.Conclusions Burnout has a high prevalence in New Zealand’s resident doctor workforce. Several associations and qualitative themes were identified. These findings may aid in the development of interventions to mitigate burnout in the medical workforce.